2018
DOI: 10.4236/fns.2018.96051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex Differences on Temporal Sequence of Sensations after Ingesting Fruit-Flavored Tea—A Preliminary Study

Abstract: The goal of this preliminary study was to examine the effect of participants' sexes on the temporal sequence of dominant sensations elicited by fruit-flavored teas. Twelve healthy young adults were assigned to male (n = 6) and female (n = 6) groups. Both groups were evaluated for four sensations using four fruit-flavored teas with 0.05 M sucrose using the temporal dominance of sensations (TDS) method. Only two sensations, sweetness and fruitiness, were consistently reported in the two groups. The male group fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Besides, these studies paid little attention to the influence of participants' sex on the results (e.g., 10 females and one male [5]). Our recent study documented sex-based differences in the temporal sequence of sweetness and fruitiness in sweetened and strawberry-flavored teas with the TDS method [1]. This study suggested that the sucrose concentration plays an important role in determining the temporal sequence of sensations.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Besides, these studies paid little attention to the influence of participants' sex on the results (e.g., 10 females and one male [5]). Our recent study documented sex-based differences in the temporal sequence of sweetness and fruitiness in sweetened and strawberry-flavored teas with the TDS method [1]. This study suggested that the sucrose concentration plays an important role in determining the temporal sequence of sensations.…”
Section: Introductionmentioning
confidence: 80%
“…Since sweetened black teas commercially available in Japan contain 0.05-M sucrose on average [10], our preceding study [1] used that concentration of sucrose to match the commercial teas. This study suggested that the sex of participants could affect the temporal sequence of the two major sensations, sweetness and fruitiness, elicited by flavored teas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations